"Where would I prefer to work after graduation?" Career preferences of students attending Italian nursing schools. (December 2019) - Matarese, Maria; Lommi, Marzia; Piredda, Michela; Marchetti, Anna; De Marinis, Maria Grazia
Abstract: Background: Worldwide, nursing students have reported a preference for working in intensive care, paediatrics, and operating theatres after graduation, disregarding psychiatry and geriatrics. Many factors can influence student choices. Educators need to know students' preferences and influencing factors in order to plan appropriate interventions to orient future nurses towards the clinical areas that are most in need of trained and motivated nurses. Objectives: To identify career preferences and student-related factors that influence the career intentions of students attending Italian nursing schools. Design: A cross sectional design. Setting: The study was conducted in 14 Italian nursing schools. Participants: Students enrolled on a three-year undergraduate nursing program were invited to participate. Methods: A questionnaire was used to collect sociodemographic data and clinical area preferences. A multivariate binary logistic regression was performed to identify the student characteristics influencing career choices. Results: 1534 students were enrolled in the study. Students preferred working in paediatrics, emergency departments and operating theatres, and these preferences were consistent in all of the three years. Psychiatry and geriatrics were the clinical areas least preferred in all the three years. Age, gender, nationality, and university attended were the factors that predicted students' preferences for specific clinical areas. Conclusions: In line with international literature, students attending Italian nursing schools expressed preferences for working in some clinical areas and to disregard others. Nursing curricula and internships need to be reviewed in terms of declared and hidden curriculum in order to enable students to view all areas of practice as equally valuable.